The Role of Exosomes in Cancer Progression and Therapy - Shynggys Sergazy; Roza Seydahmetova; Alexandr Gulyayev; Zarina Shulgau; Mohamad Aljofan (Biology)
Exosomes are small extracellular vesicles and are crucial in intercellular communication. Interestingly, tumor-derived exosomes carry oncogenic molecules, such as proteins and microRNAs, which can reprogram recipient cells, promote angiogenesis, and stimulate cancer pre-metastatic niche, supporting cancer growth and metastasis. On the other hand, their biocompatibility, stability, and ability to cross biological barriers make them attractive candidates for drug delivery. Recent advances have shown the potential for exosomes to be used in early disease detection and in targeted drug therapy by delivering therapeutic agents specifically to tumor sites. Despite the promising applications, a number of challenges remain, including exosome isolation and characterization, as well as their inherent heterogeneity. Thus, the current review aims to describe the roles of exosomes in health and disease, and discuss the challenges that hinder their development into becoming useful medical tools.